Sex, crime and urbanism as motifs of violence in selected thriller fictions of Leye Adenle (2023)
Leye Adenle’s thriller fictions, Easy Motion Tourist and When Trouble Sleeps, complement Nigeria’s creative writing landscape with recourse to distinct issues in contemporary Nigerian society, which serve as setting in the two novels. Against the backdrop of a rising spate of creative writing in Nigeria, attention is therefore paid to these literary specimens in relation to how the issues of sex and crime underscore the motif of violence. This study therefore investigated the tropes of sex, crime and urbanism as motifs of violence in Adenle’s popular fiction. The selected texts foregrounded the writer’s sense of creativity and imaginative prowess in establish-ing the connection between creative writing and society. Having underscored the rising tempo of Nigerian Thriller fiction in relation to critical issues raised in the texts, this research further established the relationship between literature and the society. Using Aspect of Cultural Studies theory, this study through these texts revealed critical reflections of the Nigerian society in contemporary times through critical investigation of salient thematic preoccupations connected to the notions of sex, crime and urbanism as catalyst which led to streams of violence in the novels. Further findings articulate a critical exploration of inherent literary tropes in the selected thriller texts, which pontificates towards popular fiction as a thriving genre in the Nigerian literary space.